Polyphenols differentially inhibit degranulation of distinct subsets of vesicles in mast cells by specific interaction with granule-type-dependent SNARE complexes - Yang, Yoosoo; Oh, Jung-Mi; Heo, Paul; Shin, Jae Yoon; Kong, Byoungjae; Shin, Jonghyeok; Lee, Ji-Chun; Oh, Jeong Su; Park, Kye Won; Lee, Choong Hwan; Shin, Yeon-Kyun; Kweon, Dae-Hyuk (PORTLAND PRESS LTD, 2013)
Anti-allergic effects of dietary polyphenols were extensively studied in numerous allergic disease models, but the molecular mechanisms of anti-allergic effects by polyphenols remain poorly understood. In the present study, we show that the release of granular cargo molecules, contained in distinct subsets of granules of mast cells, is specifically mediated by two sets of SNARE (soluble N-ethylmaleimide-sensitive factor attachment protein receptor) proteins, and that various polyphenols differentially inhibit the formation of those SNARE complexes. Expression analysis of RBL-2H3 cells for 11 SNARE genes and a lipid mixing assay of 24 possible combinations of reconstituted SNAREs indicated that the only two active SNARE complexes involved in mast cell degranulation are Syn (syntaxin) 4/SNAP (23 kDa synaptosome-associated protein)-23/VAMP (vesicle-associated membrane protein) 2 and Syn4/SNAP-23NAMP8. Various polyphenols selectively or commonly interfered with ternary complex formation of these two SNARE complexes, thereby stopping membrane fusion between granules and plasma membrane. This led to the differential effect of polyphenols on degranulation of three distinct subsets of granules. These results suggest the possibility that formation of a variety of SNARE complexes in numerous cell types is controlled by polyphenols which, in turn, might regulate corresponding membrane trafficking.
Keywords: FC-EPSILON-RI; SECRETORY GRANULES; HISTAMINE-RELEASE; DIETARY-INTAKE; SERUM-ALBUMIN; TEA CATECHIN; GREEN TEA; EXPRESSION; EXOCYTOSIS; RECEPTOR